Wpływ osobowości sprawcy na ocenę podstaw i zakresu odpowiedzialności karnej - Budyn-Kulik, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
A criminal act is done in certain circumstances, but it refl ects also the wrong-doer’s personality and his/her social dangerousness. The Criminal Code of 1997 replaced the term “social dangerousness” with “social harmfulness”. Art. 115 § 2 CC points out the circumstances that should be considered while assessing the level of social harmfulness; with no personality-like circumstance mentioned there. Such factor is indirectly hidden in the phenomena of motivation. While one considers acts that are done mostly because of some external situation-related factors, the wrong-doer’s personality does not matter. One’s personality should be considered as far as involuntary acts are concerned. The wrong-doer’s personality is interesting for criminal law purposes, because of some terms the Polish CC uses, like personal characteristics Art. 10 § 2, 10 § 4, Art. 21 § 1 i § 2, Art. 58 § 2a, Art. 66 § 1, Art. 69 § 2, Art. 77 § 1, Art. 53 § 2 and motivation Art. 40 § 2, Art. 53 § 2, Art. 115 § 2, Art. 148 § 2 point 3. The term “personal characteristics” is wider than “personality”. There are many psychological theories that try to explain what personality is Freud’s, factors, cognitive, social learning, humanistic and systematic theory. Personality is a fairly well-fixed regulation system that starts to function about the age of 21. It consists of many elements. Personality can change drastically during lifetime under certain traumatic circumstances, organic brain changes or addictions to psychoactive substances. The act of a wrongdoer may express his/her typical characteristics personality but it may not be so typical for him/ her, either. Usually, when it is typical the court treats it as an aggravating circumstance and when untypical — as a mitigating one. Personality issues need some specialist knowledge. Personal characteristics are important as far as criminal liability is concerned. Otherwise, their presence should be limited in the Criminal Code and used only in Art. 10 § 2 and Art. 53. They should be considered as far as the period of punishment execution and probation measures are concerned.
Keywords: osobowość; szkodliwość społeczna; cechy osobiste; odpowiedzialność karna; wyrok